(untitled) (Research, Society and Development, 2021)
Breast cancer is a disease with a progressive incidence rate with advancing age, which can affect both women and men. The lack of knowledge about breast cancer in men prevents the male population from seeking health services, triggering a late diagnosis, reducing the chances of cure. Therefore, the objective was to analyze the perception of men about the occurrence of breast cancer in men, describing the epidemiological profile, through the social and demographic characteristics of the research participants. For this, a structured questionnaire was developed with questions related to sociodemographic data and questions about specific aspects of breast cancer. The collected data were analyzed using descriptive statistics with the aid of the Microsoft Office Excel program. As a result, it was observed that most men know the disease, however, they are unaware of the occurrence in the male audience. The participants’ lack of knowledge may be related to the fact that most prevention campaigns are aimed at the female public and the lack of male knowledge when considering themselves invulnerable, and they seek the doctor only in the presence of symptoms of the disease. It is concluded that the lack of information and prevention campaigns for the disease directed at the male public generate a great problem, contributing to the carelessness in the search for preventive health care.